Sensors for Automotive and Aerospace Applications - Bhattacharya, Shantanu; Agarwal, Avinash Kumar; Prakash, Om; Singh, Shailendra (Energy, Environment, and Sustainability, 2019)
This volume covers the various sensors related to automotive and aerospace sectors, discussing their properties as well as how they are realized, calibrated and deployed. Written by experts in the field, it provides a ready reference to product developers, researchers and students working on sensor design and fabrication, and provides perspective on both current and future research.